EFFECTS OF USING BIOMETRICS AS AUTHENTICATION TOOL IN SECURITY SYSTEMS IN THE DEVELOPING COUNTRIES - Otubo, Kingsley (IJRDO -Journal of Computer Science Engineering, 2020)
The developing countries have been faced with a lot of security challenges in the world today. Security threats in areas of food, Lives, climates, and properties have remained a thorn in the flesh in developing countries. One of the greatest concerns among the inhabitants of Nigeria as one of developing countries of the world today is how to secure Lives and properties of the citizenry. The introduction of Biometrics security technology into access control systems and other security mechanisms has brought big relief to the society. Biometrics uses the physiological and behavioural characteristics of a person to properly identify him and help to tell the class of person he belongs based on the available data.  Sometimes these treats are adversely affected in the developing countries. We used verification and authentication methodology to verify how  fingerprints and facial screening can explore the different aspects of the face structure and pattern of arrangement of the fingerprint ridges that implement a unique personal identification system are used against the owner. It measures the different components of the face structure, such as the nose position, the mouth, the distance of the left eye to right eye and the actual location of the eyes to the mouth, nose, and the fingerprint ridges and its bifurcations etc and stores the bio-information extracted from every person that enrolls in a database. These form the basic identification data. It has increased  denial of access to personal data and right of ownership to personal properties.  It has also reduced unauthorized access to confidential documents.